Synthesis, characterization and thermal behavior of some Zn(II) complexes with ligands having 1,3,4-thiadiazole moieties - Turan, Nevin; Şekerci M. (My University, 2010)
Some new zinc(II) complexes of the type [Zn(L1) 2(C2H5OH)2]·C 2H5OH, [Zn(L2)2 Cl 2]·H2O, and [Zn2(L3)2(H 2O)4Cl4], where HL1 = N-[5?-amino-2, 2?-bis(1, 3, 4-thiadiazole)-5-yl]-2- hydroxybenzaldehyde imine, L2 = N-(5-ethyl-1, 3, 4-thiadiazole-2-yl) terephthalaldehyde imine, and L3 = N, N?-bis[5-(4-nitro phenyl)-1, 3, 4-thiadiazole-2-yl]terephthalaldehydediimine have been synthesized and characterized by IR, 1H NMR spectra, elemental analyses, magnetic susceptibility, UV-vis. and thermogravimetry-differential thermal analysis (TGA-DTA). On the basis of electronic spectral studies, an octahedral environment around the Zn(II) ion has been suggested. 1H NMR spectra of the metal complexes of ligands were found to be in agreement with the proposed stoichiometry. The presence of water molecules and ethanol in the Zn(II) complexes is also indicated by the thermal studies. © 2010 Wiley Periodicals, Inc.